Answer:
x ≈ 1.32, x ≈ - 5.32
Step-by-step explanation:
Given
x² + 4x - 7 = 0 ( add 7 to both sides )
x² + 4x = 7
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(2)x + 4 = 7 + 4
(x + 2)² = 11 ( take the square root of both sides )
x + 2 = ±
( subtract 2 from both sides )
x = - 2 ± ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Thus
x = - 2 -
≈ - 5.32 ( to 2 dec. places )
x = - 2 +
≈ 1.32 ( to 2 dec. places )
Answer:
x = 5
Step-by-step explanation:
6(3 - 7x) = -192
Divide each side by 6
6/6(3 - 7x) = -192/6
3 - 7x = -32
Subtract 3 from each side
3-7x-3 = -32-3
-7x = -35
Divide each side by -7
-7x/-7 = -35/-7
x = 5
Answer:
10
Step-by-step explanation:
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions here.
If Sarah is saving to buy a new phone. She needs $150, and she has already saved $63 then the equation should be $63 + x = $150